Manajemen Kepemimpinan Timotius: Nilai, Tantangan, dan Relevansinya bagi Pembentukan Karakter Mahasiswa Kristen - Mersi Faot; Ade Tiara; Yulika Yulika; Yulina Yulina; Sarmauli Sarmauli (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This article aims to explore the leadership management of Timothy, a young leader in the Bible, by examining his values, principles, challenges, and the relevance of his leadership for contemporary Christian students. The study employs a qualitative literature review method by analyzing the books of 1 and 2 Timothy, supported by relevant management and theological literature. The findings reveal that Timothy’s leadership is characterized by faithfulness, exemplary living, humility, courage, spiritual discipline, and a strong commitment to maintaining the purity of Christ’s teachings. In facing challenges such as false doctrines, social pressures, and limited congregational support, Timothy demonstrated managerial skills grounded in faith and obedience to the guidance of the Apostle Paul. The study highlights that Timothy’s leadership principles remain highly relevant for Christian students today in developing integrity, resilience, and service-oriented leadership. Furthermore, his example provides valuable insights into integrating spiritual management within academic and organizational contexts. This article contributes to a deeper theological understanding of leadership management that unites faith-based values, moral responsibility, and practical competence to respond wisely and ethically to the challenges of modern life.